(untitled) (Diyala Journal of Engineering Sciences, 2014)
Here in this study it is assumed that an undetected large size boulder, has a sharp edge and projecting upwards making a “point force or a point reaction,” and exists directly under domestic footing. The beam on elastic foundation (Hetenyi-solution, 1946) will change to different spring constants reflecting soil and boulder strength properties, and in this way the problem is analyzed numerically in FE method using STAAD-Pro/2004 program. The usual stresses and strains existing in concrete footing will eventually change, the case which this study may show. In other words, the study is concerned in the stress distribution in soil with the presence of boulder and in modeling it into the FE method as spring forces, and how these induced forces will change the stresses and strains in the footing concrete by comparing it with the case of non-boulder existence. The integrity of footing is noticed to see how much domestic footing is close to jeopardy. It is concluded that there is high increase in stress over the designed one if there exists a boulder rock underneath footing. In extreme cases these percent stress increase will eventually exceed 100%.